Avaliando o estabelecimento e a manutenção de classes de equivalência e da transferência de função em pessoas com e sem depressão - Zapparoli, Heloisa Ribeiro (2021)
Depression is highly prevalent in the world, affecting approximately 4.4% of the population. Depressed individuals underperform on memory tasks, but they are more likely to remember negative stimuli. On the other hand, studies with nondepressed people using the stimulus equivalence paradigm have shown that positive valence stimuli may favor the stability of equivalence classes and transfer of function between its members. The present study aimed to evaluate the formation and maintenance of equivalence classes as well as the transfer of function between meaningful stimuli of different valences and abstract stimuli, in depressed and nondepressed participants. For this purpose, 72 participants were assigned to four different groups after the administration of the Beck Depression Inventory - II. Two experimental groups (depressed and nondepressed) were given 1) matching-to-sample procedures to establish and to evaluate the formation of three four-member classes, each containing pictures of sad, happy and neutral faces in addition to abstract stimuli, and 2) the Semantic Differential and the Implicit Relational Assessment Procedure (IRAP), for evaluating the transfer of function between stimuli. Thirty days later, the tests were repeated in a follow-up session to verify the maintenance of results. Two control groups (depressed and nondepressed) evaluated only the experimental stimuli using the Semantic Differential. Group analysis indicated that depressed and nondepressed participants demonstrated the formation and maintenance of equivalent stimulus classes. Individual results, however, indicated that the number of depressed participants who had more difficulties in baseline training and class formation tests was higher than the number of nondepressed participants. Both groups demonstrated transfer of function in the Semantic Differential in the two experimental sessions. The groups differed only in the evaluation of the abstract stimulus equivalent to the happy face made in the follow-up session (maintenance), which was more positive for the depressed group. IRAP results showed that the groups differed in the first session, in which the nondepressed group showed a single trial type dominance effect for the positively valenced stimuli. For the depressed group, this trial type did not differ from the trial type that contained the negatively valenced stimuli. These data extend the literature on formation and maintenance of equivalence classes and transfer of function, including results from depressed and nondepressed participants.